Clinical Profiles of Patients with Keratoconus Visiting a Tertiary Eye Center in Kuala Lumpur, Malaysia - Norsyariza Razak; Bariah Mohd Ali; Wan Haslina Wan Abdul Halim (Journal of Current Ophthalmology)
Purpose: To evaluate the demography, clinical characteristics, and risk factors of keratoconus (KCN) patients attending a tertiary eye center in Kuala Lumpur, Malaysia. Methods: This prospective cross-sectional study included KCN patients who visited Ophthalmology Clinic, Hospital Canselor Tuanku Muhriz UKM, Kuala Lumpur, Malaysia between January 2022 and October 2023. Their demographic details, best-corrected visual acuity (BCVA), clinical findings, refraction, and risk factors were recorded. Topographical data and KCN classification were obtained through Oculus Pentacam (Wetzlar, Germany). Results: Out of 71,862 cases, 78 KCN patients were identified, with the majority having bilateral KCN (75.6%). The patients were 27.90 ± 7.37 years old on average and were predominantly male (55.1%) and Malay (70.5%). The KCN severity also varied between patients (12.8% mild, 43.6% moderate, and 43.6% severe). No significant association was found between the patient’s demographics and KCN severity (P > 0.05). The patients had a mean BCVA of 0.39 ± 0.48 and a mean spherical equivalent of −5.30 ± 4.45. Eye rubbing (85.9%) and atopy (80.77%) were identified as the most common risk factors for KCN, contrary to family history (12.8%). Meanwhile, Scissors Movement, Vogt Striae, and Munson’s Sign were among the highest percentages of clinical findings presented. Furthermore, 68.7% of KCN cases also reported ocular allergies (papillae). Conclusion: Patients’ demographics were not a determinant of KCN severity. Eye rubbing and atopy were the most significant risk factors for KCN in Malaysia. Thus, KCN screening for patients with atopy and ocular allergies is vital for KCN prevention.